EFFORTS TO IMPROVE STUDENT LEARNING ACTIVITIES THROUGH THE PROVISION OF INFORMATION SERVICES IN SMPN 2 METRO IN LESSON 2013/2014 - Tukilah, Tukilah (Universitas Muhammadiyah Metro, 2016)
Goals to be achieved researchers that want to know the provision of information services can improve students' learning activities in class VII SMP Negeri 2 Metro Semester Academic Year 2013/2014. The design of this research using action research service. The subject in this study is a Class VII the number of students is 20 students. The results of this study, it can be concluded that the information services in improving student learning activities Class VII SMP Negeri 2 Metro is we can see from this change in behavior of students there is an increase in students' learning activities that occur on the first cycle of 39.5% and the second cycle by 76%, resulting in an increase of 36.5%.Keywords: learning activities, information services, smp negeri 2 metro